2020
DOI: 10.1186/s12879-020-05621-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Streptococcus suis Meningoencephalitis with metagenomic next-generation sequencing of the cerebrospinal fluid: a case report with literature review

Abstract: Background Streptococcus suis meningoencephalitis is a zoonotic disease that mostly infects slaughterhouse workers. Rapid diagnosis of Streptococcus suis meningoencephalitis is critical for effective clinical management of this condition. However, the current diagnostic techniques are not effective for early diagnosis of this condition. To the best of our knowledge, the use of cerebrospinal fluid metagenomic next generation sequencing in the diagnosis of Streptococcus suis meningoencephalitis has been rarely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…mNGS is a novel and promising approach in diagnostic microbiology having the ability to detect many potential microorganisms using a single assay ( 7 , 25 ). Previous studies show that mNGS of CSF obtained from patients with central nervous system infections improved the diagnostic rate and provided actionable information ( 26 , 27 ). In this case, the mNGS detected the pathogens in time and provided a direction for us to identify the source of infection.…”
Section: Discussionmentioning
confidence: 99%
“…mNGS is a novel and promising approach in diagnostic microbiology having the ability to detect many potential microorganisms using a single assay ( 7 , 25 ). Previous studies show that mNGS of CSF obtained from patients with central nervous system infections improved the diagnostic rate and provided actionable information ( 26 , 27 ). In this case, the mNGS detected the pathogens in time and provided a direction for us to identify the source of infection.…”
Section: Discussionmentioning
confidence: 99%
“…So Traditional diagnostic methods are routine, sophisticate, and sometimes insensitive to adequately diagnose the infectious agents [ 19 ]. To better identify the causative agents, several molecular biological techniques such as PCR, real-time PCR or WGS have been applied for diagnosis [ 19 – 21 ]. A study designed to verify the usefulness of multiplex PCR in identifying S. Suis infection demonstrated that this technique can detect S. suis directly from positive hemocultures and CSF, with high sensitivity, specificity compared to culture and serotyping methods.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2019 to verify the real-life usefulness of mNGS in intracranial infection indicates that clinical metagenomic NGS of CSF represents a potential step forward in the diagnosis of meningoencephalitis [ 22 ]. In S. suis infection, there are also several case reports making use of mNGS to identify Streptococcus suis in cerebrospinal fluid and blood samples [ 21 , 23 ] It is worth noting that in these cases, conventional microorganism detection methods are usually negative. But currently it remains difficult to roll out this technology in countries with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diagnosis, it is especially useful when disease etiology is unclear or the list of potential pathogens is broad. Some examples of the identification of viruses [ 18 ] and bacteria [ 19 ] by this method have been reported. Platforms from Illumina, Thermo Fisher, and Pacific Biosciences require proper logistics and high investment as well as trained personnel.…”
Section: State-of-the-art Of Diagnostic Tests For Bacterial Pathogmentioning
confidence: 99%